2016
DOI: 10.1136/jmedgenet-2016-103988
|View full text |Cite
|
Sign up to set email alerts
|

SLC13A5is the second gene associated with Kohlschütter–Tönz syndrome

Abstract: We conclude that SLC13A5 is the second major gene associated with the clinical diagnosis of KTZS, characterised by neonatal epileptic encephalopathy and hypoplastic AI. Careful clinical and dental delineation provides clues whether ROGDI or SLC13A5 is the causative gene. Hypersensitivity of teeth as well as high caries risk requires individual dental prophylaxis and attentive dental management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 40 publications
10
70
1
1
Order By: Relevance
“…A recent study further demonstrated the association of SLC13A5 mutations with Kohlschütter–Tönz syndrome, characterized by epileptic encephalopathy, intellectual disability and amelogenesis imperfecta (AI), hereditary disorders with developmental abnormalities in the quantity and quality of enamel [26, 27]. In the current study, abnormalities in teeth and bone of Slc13a5 deficient ( Slc13a5 -/- ) mice were characterized.…”
Section: Introductionmentioning
confidence: 70%
“…A recent study further demonstrated the association of SLC13A5 mutations with Kohlschütter–Tönz syndrome, characterized by epileptic encephalopathy, intellectual disability and amelogenesis imperfecta (AI), hereditary disorders with developmental abnormalities in the quantity and quality of enamel [26, 27]. In the current study, abnormalities in teeth and bone of Slc13a5 deficient ( Slc13a5 -/- ) mice were characterized.…”
Section: Introductionmentioning
confidence: 70%
“…Whether the consanguinity of parents has any bearing on disease penetrance is yet another area that remains to be addressed because the severity of clinical presentations may vary as a result of the cumulative effect of detrimental genetic aberrations in different in-bred generations. To address these issues, further clinical and genetic characterizations of patients with KTS by including the SLC13 A5 (SoLute Carrier family 13, subtype 5) gene, which was recently shown to be mutated in patients negative for ROGDI mutations, 12 from ethnically defined patients is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, according to the report, mutation in the SLC13A5 gene, which encodes a sodium-dependent citrate transporter, might also cause KTS 32 . Moreover, the ROGDI gene is reported to play an important role in tumorigenesis and the cell cycle 19, 33 .…”
Section: Discussionmentioning
confidence: 99%